First and second-order-motion perception after focal human brain lesions - Rizzo, Matthew (2008)
Perception of visual motion includes a 1st-order mechanism sensitive to luminance changes and a 2nd-order motion mechanism sensitive to contrast changes. We studied neural substrates for these motion types in 142 subjects with visual cortex lesions, 68 normal controls and 28 brain lesion controls. On 1st-order motion, the visual cortex lesion group performed significantly worse than normal controls overall and in each hemifield, but 2nd-order motion did not differ. Only 1 individual showed a selective 2nd-order motion deficit. Motion deficits were seen with lesions outside the small occipitotemporal region thought to contain a human homolog of motion processing area MT (V5), suggesting that many areas of human brain process visual motion.